2019
DOI: 10.1097/md.0000000000016103
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of prison-based cognitive behavioral rehabilitation intervention on violent sexual behaviors among sex offenders in Nigerian prisons

Abstract: Background/Objective: Evidence showed that reoffending habits are increasing among offenders with violent sexual behaviors. Given the recidivism rates, a psychotherapeutic intervention becomes imperative. This study examined the efficacy of prison-based cognitive behavioral rehabilitation intervention (PCBRI) on violent sexual behaviors among sex offenders in Nigerian prisons. Method: A total of45 participants were the sample size. Compulsive Sexual Behavior Inventory a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 21 publications
(24 reference statements)
0
31
0
1
Order By: Relevance
“…Also, in line with this study's findings, previous studies have reported the effectiveness of cognitive behavioral approaches in improving cognitive skills of different populations. [ 49 , 58 , 74 , 75 ] Similarly, earlier findings also showed that cognitive skill and behavioral disposition components influence critical thinking. [ 1 ] Exposing nursing students to critical thinking training gives an opportunity to utilize psychological assumptions in their professional practice.…”
Section: Discussionmentioning
confidence: 87%
“…Also, in line with this study's findings, previous studies have reported the effectiveness of cognitive behavioral approaches in improving cognitive skills of different populations. [ 49 , 58 , 74 , 75 ] Similarly, earlier findings also showed that cognitive skill and behavioral disposition components influence critical thinking. [ 1 ] Exposing nursing students to critical thinking training gives an opportunity to utilize psychological assumptions in their professional practice.…”
Section: Discussionmentioning
confidence: 87%
“…A significant reduction in the level of burnout among undergraduate students was found after their exposure to the group‐focused form of rational emotive behaviour coaching (Ezenwaji et al, 2019). Nwokeoma et al (2019) revealed that REOHC significantly reduced work‐related stress in a sample of the Nigerian Police Force. Onyishi et al (2021) found that REOHC had a significant effect on the management of subjective well‐being among police officers who work under stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The foregoing indicated that REBT is effective in the reduction of irrational beliefs among workers and students. Among the studies reviewed, only Nwokeoma et al (2019) determined the effect of REOHC on the management of work‐related stress management among the staff of the Nigerian Police Force, and the subjective well‐being of Nigerian police officers who work under chronic stressful conditions (Onyishi et al, 2021). Just like the Nigerian police officers, lecturers of science education in Nigerian universities work under stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Section B identified clinical/psychological characteristics namely length of the condition, severity of the condition, and duration of condition. Besides the items of the instrument adapted from , a good number of studies were reviewed to build up the demographic and clinical characteristics of the participants (Ede et al, 2020a;Nwokeoma et al, 2019a). The authors argued that in clinical case like this, psychological/clinical characteristics are required to understand possible predictors of the condition.…”
Section: Methodsmentioning
confidence: 99%